Progress in implementing European policy priorities for vocational education and training in the Copenhagen process (2002 - 2010) : Questionnaire to the Directors General for Vocational the Copenhagen process (2002 - 2010) : Questionnaire to the Directors General for Vocational Training : Austria - (:unkn) unknown (My University, 2009)
"Der österreichische Report über den Kopenhagen-Prozess in der Berufsbildung 2002 bis 2010 umfasst folgende neun Themen: Theme 1 Progress in modernising European VET systems in the Copenhagen process and priorities for future cooperation; Theme 2 Socioeconomic challenges and priorities for future VET policy development; Theme 3 Economic crisis - VET policies as recovery measures; Theme 4 Impact and implications of joint work on European principles and tools; Theme 5 Strengthening links between VET and the labour market; Theme 6 Addressing equity, social inclusion and active citizenship; Theme 7 Quality, excellence and attractiveness of VET; Theme 8 Enhancing creativity and innovation; Theme 9 Financing VET." (öibf, BIBB-Doku)
Keywords: S System beruflicher Bildung; G 1.2 Arbeitsmarkt; S 4.1 Finanzierungsquellen; I 2.2.1 Westeuropa; Berufsbildung; Sozioökonomische Faktoren; Arbeitsmarkt; Bildungsfinanzierung; Europäische Integration; Berufsbildungssystem; Österreich